2016
DOI: 10.1111/eos.12277
|View full text |Cite
|
Sign up to set email alerts
|

Sodium trimetaphosphate enhances the effect of 250 p.p.m. fluoride toothpaste against enamel demineralization in vitro

Abstract: This in vitro study investigated the effect of sodium trimetaphosphate (TMP), added to toothpaste containing 250 p.p.m. fluoride, on enamel demineralization. Bovine enamel blocks (n = 96) were subjected to five pH cycles over a 7-d period and treatment with suspensions of toothpastes containing 0, 250, 500, and 1,100 p.p.m. fluoride (as sodium fluoride), as well as with 250 p.p.m. fluoride containing TMP at 0.25, 0.5, 1.0, and 3.0%. Treatment with toothpaste suspensions was performed under agitation twice a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…Despite the >4-fold difference in the F content between 250F-TMPnano and 1,100F, similar enamel F, Ca, and P concentrations were observed in enamel treated with these dentifrices. Such a trend is, indeed, in line with previous studies in which micrometric TMP was added to different low-F dentifrices (Takeshita et al 2009;Takeshita et al 2015;Missel et al 2016). The increased concentration of those Calcium 5.2E-02 a ± 2.0E-02 7.1E-02 a ± 3.9E-02 1.6E-01 b ± 7.7E-02 1.6E-01 b ± 8.6E-02 Phosphorus 1.5E-01 a ± 7.6E-02 1.2E-01 a ± 6.7E-02 1.8E-01 a ± 1.2E-01 1.8E-01 a ± 9.6E-02…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite the >4-fold difference in the F content between 250F-TMPnano and 1,100F, similar enamel F, Ca, and P concentrations were observed in enamel treated with these dentifrices. Such a trend is, indeed, in line with previous studies in which micrometric TMP was added to different low-F dentifrices (Takeshita et al 2009;Takeshita et al 2015;Missel et al 2016). The increased concentration of those Calcium 5.2E-02 a ± 2.0E-02 7.1E-02 a ± 3.9E-02 1.6E-01 b ± 7.7E-02 1.6E-01 b ± 8.6E-02 Phosphorus 1.5E-01 a ± 7.6E-02 1.2E-01 a ± 6.7E-02 1.8E-01 a ± 1.2E-01 1.8E-01 a ± 9.6E-02…”
Section: Discussionsupporting
confidence: 91%
“…Most important, while 250F-TMPnano and 1,100F dentifrices promoted similar SH values, the integrated subsurface hardness loss was significantly lower for 250F-TPMnano than for the conventional (1,100F) formulation. Because the addition of micrometric TMP to a 250F dentifrice was previously shown to produce a protective effect against enamel demineralization (SH and ΔKHN) similar to that of a conventional formulation (Missel et al 2016), the present ΔKHN findings seem to justify the use of nanoparticles instead of micrometric TMP. The more pronounced effect of nanosized TMP on ΔKHN suggests that, under clinical conditions, a subsurface lesion would take more time to develop as compared with a conventional dentifrice.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is reported that low-pH toothpastes containing 500 to 550 ppm fluoride showed similar results on enamel demineralization as the one containing 1100 ppm fluoride. 7 Dentifrice composition plays a crucial role in disabling free fluoride ions, which may lead to creation of a low-solubility product with a diminished anticaries outcome. 2,3 Currently, there are no regulations to specify how much of total fluoride should be maintained in a dentifrice formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Missel et al (14) demonstrated that the addition of phosphate in the form of sodium trimetaphosphate (TMP) to toothpaste containing (250ppm) fluoride can reduce enamel demineralization to levels similar to those seen for conventional toothpaste containing (1100ppmF) fluoride.…”
Section: Introductionmentioning
confidence: 99%